2009
DOI: 10.1126/science.1170481
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Rotavirus Outer-Layer Protein VP7 Bound with a Neutralizing Fab

Abstract: Summary The crystal structure of rotavirus VP7 bound with the Fab from a neutralizing monoclonal shows the mechanism by which members of a large class of neutralizing antibodies inhibit rotavirus infection, indicates how withdrawal of Ca2+ ions becomes an uncoating trigger during cell entry, and provides the “first draft” of a design for subunit immunogens. Rotavirus outer-layer protein VP7 is a principal target of protective antibodies. Removal of free Ca2+ dissociates the VP7 trimer, releases it from the vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
222
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(235 citation statements)
references
References 29 publications
(29 reference statements)
4
222
0
4
Order By: Relevance
“…Out of the 11 radical changes 9 were associated with changes in polarity with the strain 6788 being non-polar when compared to the consensus G9 strains. In VR-5/antigenic epitope A mutation in site 94 is associated with neutralization escape mutants (Aoki et al, 2009). Similar sites associated with neutralization escape mutants were observed in VR-8/ antigenic epitope C (positions 213, 217, 221) and in VR-9/antigenic epitope F (position 238).…”
Section: Analysis Of Vp7 Nucleotide Sequencessupporting
confidence: 50%
See 2 more Smart Citations
“…Out of the 11 radical changes 9 were associated with changes in polarity with the strain 6788 being non-polar when compared to the consensus G9 strains. In VR-5/antigenic epitope A mutation in site 94 is associated with neutralization escape mutants (Aoki et al, 2009). Similar sites associated with neutralization escape mutants were observed in VR-8/ antigenic epitope C (positions 213, 217, 221) and in VR-9/antigenic epitope F (position 238).…”
Section: Analysis Of Vp7 Nucleotide Sequencessupporting
confidence: 50%
“…Using the crystal structure of the RRV VP7 protein (PDB accession number 3fmg; (Aoki et al, 2009), amino acid substitutions found in Cameroonian strain RVA/Human-wt/CMR/ 6788/1999/G9P[8] were mapped spatially onto the 3D protein structure using the PyMOL Molecular Graphics System, version 1.5.0.1 (Schrodinger, 2010).…”
Section: Computational Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…4) (Aoki et al, 2009(Aoki et al, , 2011. The comparison investigated a total of 52 aa residues and showed the highest similarity between G10 amino acid sequences and genotypes G9 (39/52 aa) and G3 (38/ 52 aa).…”
Section: Analysis Of the Vp7 Hypervariable Regions Of G10 Rva Strainsmentioning
confidence: 99%
“…Thus, the anchored VP4 protrudes above the surface of the VP7 layer to interact with the host cells during the attachment of the virus. Proteolytic cleavage of the spike protein VP4 into VP5 * and VP8 * is required for rotavirus infectivity, with the VP8 * domain being involved in binding to cellular receptors (Aoki et al, 2009;Chen et al, 2009;Li et al, 2009;Trask et al, 2012).…”
Section: Introductionmentioning
confidence: 99%